Modified Vigenère cipher algorithm based on new key generation method - Thamer Hassan Hameed; Haval Tariq Sadeeq (Institute of Advanced Engineering and Science, 2022)
Nowadays, as communication and network technologies evolve in modern life, ensuring the confidentiality of a cryptography system has become a critical requirement. The Vigenère cipher is attracting the attention of cryptography specialists, although the Vigenère cipher algorithm has a problem. The problem is due to a repeating encryption key. As a result of the multiple cryptographic approaches described in the literature, this paper proposes a novel encryption strategy for safe and secure data exchange by utilizing a new key generation process. The proposed encryption approach avoids the issue of repeating keys. Additionally, the classic Vigenère cipher encrypts the plaintext using a 26x26 Vigenère table, the researcher modified the original Vigenère table to 95x95, which adds more potential letters, mathematical symbols, numerals, and punctuation to a standard QWERTY keyboard layout. Additionally, the researcher added case sensitivity. To observe the performance of the proposed method, the index of coincidence and entropy have been calculated. The obtained results confirm the high performance of the proposed algorithm in comparison to the other algorithms used in this paper. The primary goal of this paper is to make cryptanalysis extremely complex and to promote data security.